2003
DOI: 10.1111/j.1748-7692.2003.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability in the Proportion of Harbor Seals Hauled Out Under Locally Ideal Conditions

Abstract: We monitored the haul‐out behavior of 68 radio‐tagged harbor seals (Phoca vitulina) during the molt season at two Alaskan haul‐out sites (Grand Island, August‐September 1994; Nanvak Bay, August‐September 2000). For each site, we created a statistical model of the proportion of seals hauled out as a function of date, time of day, tide, and weather covariates. Using these models, we identified the conditions that would result in the greatest proportion of seals hauled out. Although those “ideal conditions” diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 26 publications
8
62
4
Order By: Relevance
“…For estimation of population trends, this issue has usually been addressed by either standardizing survey conditions to minimize differences in haul-out proportions (Jacobs and Terhune 2000; Simpkins et al 2003b) or adjusting for differences in conditions by incorporating appropriate covariates in models of the counts (Calkins et al 1999;Mathews and Pendleton 2006). Estimation of population size generally requires explicit estimates of the proportion of the population hauled out during the survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For estimation of population trends, this issue has usually been addressed by either standardizing survey conditions to minimize differences in haul-out proportions (Jacobs and Terhune 2000; Simpkins et al 2003b) or adjusting for differences in conditions by incorporating appropriate covariates in models of the counts (Calkins et al 1999;Mathews and Pendleton 2006). Estimation of population size generally requires explicit estimates of the proportion of the population hauled out during the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as time of day, weather, and other environmental conditions have been related to haul-out behavior of various pinnipeds (Simpkins et al 2003b;Bengtson and Cameron 2004;Frost et al 2004;Reder et al 2004;Hayward et al 2005). Walruses using terrestrial haul-out sites spend about 65%-85% of their time in the water (Born and Knutsen 1997;Gjertz et al 2001;Jay et al 2001;Born et al 2005;Acquarone et al 2006;Lydersen et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus alternative attachment methods that collect information during this period must be considered, e.g. attaching telemetry devices to the flipper (Huber et al, 2001;Simpkins et al, 2003) or by means of an implantable tag (Horning and Hill, 2005;Lander et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Harbour seals show a degree of site fidelity (Yochem et al, 1987;Thompson, 1989;, while marking studies have shown that seals use different haul-out sites throughout the year (Brown and Mate, 1983;Thompson, 1989;Thompson et al, 1996;Simpkins et al, 2003). High levels of site fidelity would support the designation of protected areas for harbour seals at haul-out sites.…”
Section: Haul-out Patterns and Site Usagementioning
confidence: 93%
See 1 more Smart Citation